Kendala Guru Bahasa Inggris Dalam Menerapkan Pembelajaran Tatap Muka Terbatas - Maria Grotty Sitohang (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This study aims to determine the obstacles of English teachers in implementing Limited Face-to-face Learning (PTMT) at SMA Negeri 1 Barumun Tengah and efforts to overcome them. This research method is a qualitative research method with a descriptive approach. The subject of this research is the English teacher of class XI, totaling 2 people. Data collection techniques in this study used interviews and documentation. The results of this study are the obstacles for the class XI English teacher in implementing PTMT, namely (1) the difficulty of the teacher in determining the appropriate, effective and efficient learning model and application. (2) decreased student interest in learning. Efforts made to overcome these obstacles (1) teachers choose learning methods and applications that are in accordance with PTMT. The Blended Learning learning model is supported by the Microsoft Sway application and Book Creator, making it easier for students to access the material presented by the teacher. (2) the teacher provides motivation, encouragement and enthusiasm to students to increase interest in learning. Many students experience loss learning during online learning. (3) Teachers and students hold effective communication to overcome the obstacles encountered during PTMT. Keywords: english teacher obstacles; limited face-to-face learning  Abstak: Penelitian ini bertujuan untuk mengetahui kendala guru Bahasa Inggris dalam menerapkan Pembelajaran Tatap Muka Terbatas (PTMT) di SMA Negeri 1 Barumun Tengah dan upaya untuk mengatasinya. Metode penelitian ini yaitu metode penelitian kualitatif dengan pendeketan deskriptif. Subjek penelitian ini yaitu guru Bahasa Inggris kelas XI yang berjumlah 2 orang. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara dan dokumentasi. Hasil penelitian ini adalah kendala guru Bahasa Inggris kelas XI dalam menerapkan PTMT yaitu: (1) kesulitan guru dalam menentukan model dan aplikasi pembelajaran yang tepat, efektif dan efesien, (2) menurunya minat belajar siswa. Upaya yang dilakukan untuk mengatasi kendala tersebut: (1) guru memilih metode dan aplikasi pembelajaran yang sesuai dengan PTMT. Model pembelajaran Blended Learning didukung aplikasi Microsoft Sway dan Book Creator mempermudah siswa mengakses materi yang disampaikan guru, (2) guru memberikan motivasi, dorongan dan semangat kepada siswa untuk meningkatkan minat belajar. Banyak siswa mengalami loss learning selama pembelajaran daring, (3) Guru dan siswa mengadakan komunikasi yang efektif untuk mengatasi kendala yang dihadapi selama PTMT.   Kata Kunci: kendala Guru Bahasa Inggris; Pembelajaran Tatap Muka Terbatas